Contextualización del reconocimiento arqueológico de Eduard Seler en la Región de Chaculá, Departamento de Huehuetenango, Guatemala - Wölfel, Ulrich (Archaeopress pre-Columbian archaeology, 2022)
This study re-examines and contextualises Eduard Seler's investigations in the Chaculá-Region, Guatemala. A new study of the Ethnological Museum Berlin's materials from the region, including previously undocumented ceramics, reveals a chronology suggesting that the major settlements were occupied from the Late Classic to the Early Postclassic.